The effect of oxytocin massage during postpartum on baby weight - Prasetya Lestari; Fatimah Fatimah; Lia Dian Ayuningrum (Alma Ata University Press, 2021)
Background:The low coverage of exclusive breastfeeding in Indonesia and the world can have a negative impact on mothers, babies, families, and even the country. Research by Rawat, et al (2018) states that one of the causes of failure of the breastfeeding process in primiparous and in the first week of delivery is that the mother finds it difficult to attach when breastfeeding and feels that breast milk is not enough. Another study conducted by Jacobs, et al (2013) also proved that the majority of respondents felt that breast milk production was scant, so they decided to provide formula milk. Meanwhile, research conducted by Madhavi and Manikyamba (2016) found that the reason for not giving exclusive breastfeeding was difficulty in the breastfeeding process. Therefore it is necessary to have a method to stimulate milk production at the beginning of postpartum, one of which is oxytocin massage. Objectives:The purpose of this study was to determine the relationship between the oxytocin massage and baby weight. Materials and methods:this study was a pre-experimental research using posttest only design and true-experiment using posttest only control group design. The research locations were in the Mother and Child Health (KIA) Clinic and Midwives Independent Practice (PMB) in Bantul, Sleman, and Gunung Kidul Yogyakarta areas. Implementation from April until September 2020. The population of this study was all the families of postpartum mothers from the first to the third day and after 1 week an evaluation of breastfeeding. The sampling technique uses total sampling was 80 postpartum mothers on the first-third day of childbirth followed until the baby was 2 months old. The research instruments were the oxytocin massage checklist and baby weight observation note sheet. Test analysis using paired t-test. Results: The results of this study were that the majority of respondents performed oxytocin massage with a frequency of 2-3 times (85%) and the majority of baby's weight at the age of 2 months was according to age (98.8%). In the results of the bivariate analysis, there was an effect of oxytocin massage education on the family of postpartum mothers with baby body weight (p = 0.009).Conclusions: Oxytocin massage education on the family of postpartum mothers there was significant with baby weight.